"True" Hydrophilic-Lipophilic Balance of Polyoxyethylene Fatty Acid Esters Nonionic Surfactants - Pasquali, Ricardo Conrado (2013)
This article proposes a set of equations that allow the calculation of the hydrophilic-lipophilic balance (HLB) value of polyoxyethylene esters from quality control data of the raw materials (fatty acids and polyethylene glycol) and the finished product (surfactant). The quality control data required include the acid value of the fatty acid, the hydroxyl value of the polyethylene glycol, and the hydroxyl value of the surfactant. Moreover, these calculations allow the determination of the mean relative molecular masses of the fatty acids, polyethylene glycol, monoesters, and diesters, and to calculate the proportion of polyoxyethylene monoester and polyoxyethylene diester. Models such as this would be of great utility for the rational design of emulsified products.